HUBUNGAN DUKUNGAN KELUARGA DAN MOTIVASI DIRI DENGAN KEPATUHAN OBAT PADA PASIEN JANTUNG KORONER DI POLI JANTUNG RAWAT JALAN RSUD DR. SOEDARSO PONTIANAK - neni octaria; Indri Erwhani; Dinar Wulan Puspita (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2018)
Abstract There is an increase in the incidence of CHD each year, which is also accompanied by an increase of mortality rate in CHD patients. The main goal of heart patients’ treatment is to relieve patients’ pain and minimize the risk of life-threatening complications. Objective: To know the relation of family support and self-motivation to drug adherence in coronary heart patients in Poli Cardiac Outpatients of Regional Public Hospital of Dr. Soedarso Pontianak. The research method used was analytic by using cross sectional approach. The samples in this research were taken using Accidental Sampling with the 166 samples. The data collection used questionnaire sheet with data analysis using Chi-square test. It was found that 94 respondents with good family support and 9 people had high adherence level and 92 respondents had good self-motivation and 14 people had high adherence level. Based on Chi-Square test, it can be concluded that there is a relation between family support with drug adherence in CHD patients in RSUD Dr.Soedarso with the value of Pvalue = 0.005 and there is a relation between self-motivation with drug adherence in CHD patients in RSUD Dr.Soedarso with the value of Pvalue = 0,003 (Pvalue <0,05). Conclusion: Family support and self-motivation are among the factor that influences drug adherence in CHD patients. Besides, family members should have appropriate knowledge about CHD diseases and drug function in CHD patients. Keywords: Family Support, Self-motivation, Drug Adherence in Coronary Heart Patients CHD). Abstrak Peningkatan angka kejadian PJK disertai dengan peningkatan angka kematian. Kepatuhan mengkonsumsi obat-obatan merupakan hal yang penting untuk menghilangkan rasa sakit dan memperkecil resiko kematian. Mengetahui hubungan dukungan keluarga dan motivasi diri terhadap kepatuhan obat pada pasien jantung koroner di Poli Jantung Rawat Jalan. Penelitian analitik dengan pendekatan crosssectional. Pengambilan jumlah sampel secara Accidental Sampling, sebanyak 166 sampel. Menggunakan lembar kuisioner dengan uji Chi-square. Hasil menunjukkan pada 94 responden dukungan keluarga baik terdapat 9 orang memiliki tingkat kepatuhan tinggi dan 92 responden motivasi diri baik terdapat 14 orang memiliki tingkat kepatuhan tinggi. Berdasarkan uji Chi-Square, ada hubungan antara dukungan keluarga dengan kepatuhan obat pada pasien PJK dengan nilai Pvalue= 0,005. ada hubungan antara motivasi diri dengan kepatuhan obat pada pasien PJK, nilai Pvalue= 0,003 (Pvalue <0,05). Dukungan keluarga dan motivasi diri merupakan faktor yang mempengaruhi kepatuhan minum obat pada pasien PJK. Anggota keluarga harus memiliki pengetahuan yang tepat mengenai penyakit PJK dan fungsi obat pada pasien PJK. Kata Kunci : Dukungan Keluarga, Motivasi Diri, Kepatuhan Obat Pada Pasien Jantung Koroner (PJK).